2021
DOI: 10.3390/ijms22168967
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin Exposure during Early Life Is Associated with Differential DNA Methylation in Two-Year-Old Gambian Children

Abstract: Background: DNA methylation is an epigenetic control mechanism that may be altered by environmental exposures. We have previously reported that in utero exposure to the mycotoxin and liver carcinogen aflatoxin B1 from the maternal diet, as measured using biomarkers in the mothers’ blood, was associated with differential DNA methylation in white blood cells of 6-month-old infants from The Gambia. Methods: Here we examined aflatoxin B1-associated differential DNA methylation in white blood cells of 24-month-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Maternal BMI and plasma nutritional biomarkers including homocysteine, folate and B12 were measured on samples collected at the time of recruitment, before supplementation (median 14 weeks gestation) 21 . Blood samples and anthropometric measures including child height were obtained from a subset of ENID children aged 2 years as part of a study identifying biomarkers and understanding mechanisms for the relationship between aflatoxin exposure and child stunting 70 . DNA was extracted from white blood cells and genome-scale methylation profiles were obtained using the Illumina Human Methylation 450K Bead Chips (450K array) as described in a previous publication 71 .…”
Section: Methodsmentioning
confidence: 99%
“…Maternal BMI and plasma nutritional biomarkers including homocysteine, folate and B12 were measured on samples collected at the time of recruitment, before supplementation (median 14 weeks gestation) 21 . Blood samples and anthropometric measures including child height were obtained from a subset of ENID children aged 2 years as part of a study identifying biomarkers and understanding mechanisms for the relationship between aflatoxin exposure and child stunting 70 . DNA was extracted from white blood cells and genome-scale methylation profiles were obtained using the Illumina Human Methylation 450K Bead Chips (450K array) as described in a previous publication 71 .…”
Section: Methodsmentioning
confidence: 99%
“…Dietary exposure to aflatoxin has also been associated with child growth impairment in several epidemiology studies [ 15–19 ]. We have recently reported that dietary aflatoxin exposure is associated with differential DNA methylation in growth factor genes and immune-related genes in Gambian children, which may play a role in aflatoxin-related growth impairment [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%